Beschaffung technischer Dienstleistungen am Beispiel Instandhaltung: Auch vermeintlich einfache Tätigkeiten können zum Desaster führen - Moritz Venschott; Hubert Vogl (IUBH Internationale Hochschule, 2020)
– In general, maintenance as part of the plant management ensures the maximum efficiency and availability of production and infrastructure plants at optimal cost and under satisfactory conditions of quality, safety and protection for the environment. Furthermore, it can be divided into four tasks, such as inspection, preventive maintenance, improvement and repair. As an economically function, maintenance has to be managed in accordance to the corporate strategy. For this reason, maintenance management has a strong strategic focus and decides e.g. which services will be outsourced (buy) or insourced (make). Like any management decision, both show strength and weaknesses as well as opportunities and treats. This discussion paper deals with the external sourcing of technical services in comparison to the services done by own maintenance staff. First, the basics of maintenance and maintenance management like make or buy and the procurement process are outlined. Afterwards, the risk analysis is introduced and applied. Several potential risks were identified and explained in detail. For each risk, several compensate measures were introduced and the individual impact is discussed.
Keywords: 650; Dienstleistungssektor; Instandhaltung; Beschaffung; Kompetenzen; Qualitätsmanagement; Risikoanalyse